Expert System for Chiller Machine Damage Detection Using Forward Chaining Algorithm - Achmad Noeman; Atsal Adriansyah; Abrar Hiswara; Dian Hartanti; Prio Kustanto; Hafizah Hafizah (LPPM Universitas Islam 45 Bekasi, 2024)
The causes of damage to the chiller machine can be sorted in a logical sequence to find the cause of damage to the chiller machine, so that users can immediately find out the cause of the existing damage. An expert system is a computer program that contains knowledge from one or more human experts about a specific field. With this system, it is hoped that users can easily find out about damage and how to handle it on the machine. Observations were carried out directly on the research object, namely PT Indofood CBP, because the way to observe the research object is to understand the needs of the research object so that the system built can meet the needs of the user concerned. Starting from minor problems to serious problems, apart from that, we also test the running of the chiller until the operation of every machine that requires supply from this chiller machine. This system was created with the aim of making it easier for users if they experience difficulties in carrying out repairs or troubleshooting the chiller machine. So that you can get solutions based on previous experiences carried out by Engineers. After collecting analytical data to overcome troubleshooting, the design stage is carried out to create an expert system for detecting damage to machines and how to handle repairs based on the experience that has been provided.